Phytochemical analysis of Flacourtia ramontchi (Salicaceae) - Mamy, Andrianarijaona; Fabri, Ralaivaon-dratsitonta Jumaël Edith; Ruphin, Fatiany Pierre; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
Flacourtia ramontchi is a medicinal plant deeply rooted in the traditional practices of Madagascar, where a decoction from its leaves and bark is commonly used to treat respiratory ailments such as asthma and dry coughs. The present study was conducted to provide a scientific foundation for these traditional uses by performing a comprehensive phytochemical analysis. The investigation involved the successive maceration of powdered bark and leaf samples using a series of solvents of increasing polarity, namely n-hexane, dichloromethane (DCM), and methanol. This extraction process yielded a variety of crude extracts, with the highest yields for both plant parts obtained from the non-polar hexane solvent, suggesting a rich presence of non-polar constituents. Phytochemical screening of the extracts identified a significant abundance of secondary metabolites with recognized therapeutic value. The bark and leaves were particularly rich in polyphenols, tannins, and flavonoids, compounds known for their antioxidant, anti-inflammatory, and antimicrobial properties, which scientifically validate the plant's traditional medicinal applications. Following the preliminary screening, the DCM bark extract was selected for further separation and purification. Thin-layer chromatography (TLC) was optimized to an ideal hexane/DCM (30:70) mobile phase, revealing four dominant constituents. This strategic approach led to the subsequent isolation of a pure compound via column chromatography. The fraction with the highest yield was chosen for structural elucidation. The structure of the isolated compound was determined using mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopy, including ¹H NMR and ¹³C NMR. Spectral data analysis, specifically the molecular ion peak in the mass spectrum at m/z 300 and the carbon and proton signals from the NMR data, confirmed the compound to be spruceanol, a diterpenoid. This finding is a significant contribution to the understanding of the plant’s chemical composition.